The Role Of Psychological Accompaniment In Enhancing Mental Health In Mothers Of Children With Autism Spectrum Disorder - Hamdi Bacha ,Yasmine; Benseghir, Karima (University of Eloued جامعة الوادي, 2024)
The precautionary principle is defined as the principle that obligates not to invoke the absence of scientific certainty when it comes to the harmful effects of activities to refrain from taking the necessary precautionary measures or delay in taking them to avoid the occurrence of such damages. By examining the precautionary principle in the medical domain, it appears at first sight that it is opposed to and opposite to the civil liability of doctors, with reason of the compensable nature of damages within the framework of this liability, which requires that the damage be direct, fixed and verified, overtly certain. All of this is inconsistent with the application of the precautionary rules, It requires that the danger is not scientifically certain on the one hand, and on the other hand, that The precautionary principle appears before the damage occurrence, while civil liability, in addition to the compensation system that it decides, engender later, so after the damage has occurred, which creates a contradiction between them.
Keywords: The precautionary principle; scientific uncertainty; medical liability; risk; – damage; objective civil liability